Peningkatan Keselamatan Masyarakat Melalui Pemasangan Kaca Cembung Di Wilayah RT 5 RW 9 Kelurahan Pematang Gubernur - Putri, Shofi Rahmadannia; T, Oscar Julius Gamaliel; Atharrafly , Muhammad; Andini , Fira Juli; Prananda , M. Akbar; Putra , Dwingki Marta; Irwanto, Tito; Abi, Yudi Irawan (Utami Publisher, 2025)
This community service project aimed to improve traffic safety in the densely populated area of RT 09 RW 05, Pematang Gubernur Subdistrict, through the installation of convex mirrors at a hazardous three-way intersection. The primary issue identified by local residents was limited visibility at road corners, which frequently led to near collisions. Using a collaborative approach, this activity involved active community participation in all stages, including problem identification, location determination, installation, and impact evaluation. The results showed that the presence of convex mirrors significantly enhanced driver awareness, improved traffic behavior, and fostered a collective sense of responsibility among residents regarding environmental safety. In addition to its functional benefits, the program strengthened community ownership of public facilities through participatory implementation. Thus, the collaborative approach proved to be effective in supporting sustainable, community-based traffic safety initiatives and may be replicated in other areas with similar conditions.